Hak Anak dan Pola Asuh Pasca Perceraian di Kecamatan Mungkajang Kota Palopo Perspektif Fikih Parenting - Muchtar, Zulayka; Marwing, Anita; Nur, Muhammad Tahmid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This study aims to analyze children's rights and parenting patterns in post-divorce in Mungkajang Sub-district, Palopo City. This research was analyzed by descriptive qualitative with a religious approach (fiqh parenting, parenting jurisprudence). Data were collected through documentation and interviews with parents and children. The results showed that: (1) the form of fulfilment of children's rights after divorce in Mungkajang District is divided into: democratic parenting (fulfilment of children's rights from the father), authoritarian parenting (fulfilment of children's rights from the mother) and permissive parenting (fulfilment of children from the father and mother), and children at an individual stage; (2) Factors that influence parenting patterns that come from fathers are parental relationships and parental age with a model of practicing children's worship in the form of the implementation of 5-time prayers and Ramadan fasting that is well implemented, and the implementation of reading the Koran 2 to 3 times a week; Factors influencing parenting patterns originating from mothers are the involvement of parents with a model of practicing children's worship in the form of the implementation of 5-time prayers and fasting Ramadan which is well implemented, and the implementation of reading the Koran is uncertain; and factors influencing parenting patterns originating from both parents are the age of parents and the practice of parenting children with a model of practicing children's worship in the form of 5-time prayers, fasting and reading the Koran has been going well.